Research into curriculum development at ten theological institutions of Reformed tradition in sub-Saharan Africa linked to NetACT - Du Preez, Kruger P; Hendriks, Jurgens H; Carl, Arend E (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Between 2006 and 2013 an empirical study of the curriculum development (CD) of ten NetACt theological institutions of Reformed tradition in sub-Sahara Africa was done. The researchers visited all the campuses and did curriculum development workshops (CDW) with the institutions. Questionnaires addressing worldview, value systems, missional direction, contextualisation and educational principles were used to get basic information. The research found positive learning environments on the campuses with dedicated lecturers and students. The curricula reflect that suffcient attention is given to modernism, secularism, urban and rural evangelism while a deliberate attempt is made to improve the analytical thinking skills of the students. HIV and AIDS courses are found on every campus and there is a new awareness of the importance of Community Development. However, the research also found that the curricula do not reflect emphasis on issues like poverty and children ministry. The majority of the institutions admit to discrimination against women. Nearly all institutions used curricula copied and adapted from Western institutions and added new material on an ad-hoc basis. In many cases there are no written outcomes for modules, no assessment plan and in general a lack of quality control. The success stories of the NetACt curriculum workshops are told and useful recommendations are made for the improvement of curricula.